Pre‐Cenomanian vs. Cenozoic folding in the High Atlas revealed by palaeomagnetic data. (21st January 2016) - Torres‐López, Sara; Casas, Antonio M.; Villalaín, Juan José; El Ouardi, Hamidou; Moussaid, Bennacer
Abstract: Palaeomagnetic data, and specifically remagnetizations, are used to constrain the geometric reconstruction at 100 Ma of three anticlines cored by gabbroic intrusions and Triassic shales in the Central High Atlas, Morocco. Previous palaeomagnetic results have revealed that the Mesozoic sediments of this region acquired a pervasive remagnetization at the end of the Early Cretaceous. The restoration of palaeomagnetic vectors to the remagnetization stage (100 Ma) allows us to determine the dip of the beds during this period and, thereby, to reconstruct structures during that time and determine the relative contributions of Mesozoic magmatic/diapiric uplift vs. Cenozoic compression to the present‐day dip. Our results indicate that three major anticlines in the Central High Atlas (Tasraft, Tassent and Tissila) were initiated to different degrees before the Late Cretaceous and were reactivated during Cenozoic compression to acquire their present‐day geometry. We also discuss the origin of these structures.